2021
DOI: 10.4038/rjs.v12i1.100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rainfall trends and variabilities for three decades in Sub – Sahara Africa

Abstract: Rainfall trend is an important climatic factor that influences agricultural products, groundwater production, drainage planning, commercial and industrial activities. The research aims to determine the trends and variability of monthly, seasonal, and annual rainfall for 30 years (from 1980 to 2010) in Sokoto (13.0059° N, 5.2476° E) and Maiduguri (11. 8333° N, 13.1500° E) using archives data obtained from the Nigeria Meteorological Agency (NiMet), Oshodi Lagos Nigeria. Statistical models were used to analyze th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Furthermore, ARIMA models have been shown to be one of the most widely utilized models for a variety of applications, including science, technology, economy, market, commerce, and industry [4,6,7]. ARIMA models, in particular, have been found to be effective in forecasting various weather conditions [26]. [20] revealed linear ARIMA model and quadratic model as the overall best performing model for the prediction of the monthly and annual temperature in Libya.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ARIMA models have been shown to be one of the most widely utilized models for a variety of applications, including science, technology, economy, market, commerce, and industry [4,6,7]. ARIMA models, in particular, have been found to be effective in forecasting various weather conditions [26]. [20] revealed linear ARIMA model and quadratic model as the overall best performing model for the prediction of the monthly and annual temperature in Libya.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies carried out on rainfall time series across the world revealed that the effect is positive and negative on the trends of rainfall [6]. Xu et al [11], Wang et al [12], Anghileri et al [13] and Aweda et al [14] expressed different analyses on the trend of rainfall and its fluctuations through diverse places across the entire world. Nevertheless, period sequence study of rain shown either reducing or accumulating rainfall, depending on the place [15].…”
mentioning
confidence: 99%
“…On May 1 st 2023, HelioClim-1 data used for the study years was accessed for all the stations considered, that is, Abuja, Cairo, Nairobi, Pretoria, and Yaoundé . Furthermore, the data used ranges from 1980 to 2022 were collected as a monthly average for January through December of each year in comma-separated value (CSV) format, according to Aweda et al [2,29].…”
Section: The Process Of Data Collectionmentioning
confidence: 99%